Soporte familiar y adaptación a la vida universitaria de estudiantes de la Escuela Profesional de Arquitectura y Urbanismo, Universidad Nacional de Trujillo, 2021 - Rodríguez Vásquez, Thania Lisset (2023)
This research was carried out with the aim of analysing the influence of family support in the adaptation to university life of students of the Professional School of Architecture and Urbanism, National University of Trujillo, 2021. The sample consisted of 40 first year students of the Professional School of Architecture and Urbanism of the National University of Trujillo with an age range between 17 and 24 years, in the same way three methods were applied as the inductive - deductive, analytical - synthetic and statistical; the techniques used were the interview and the survey applied by means of the instruments of the questionnaire, the interview guide and the interview register. According to the results obtained, it is shown that family support has a positive influence on the process of adaptation to university life, evidenced by the support for autonomy and the organisation of the academic activities of the students of Architecture and Urbanism of the National University of Trujillo.